Quality Analysis of PDCA-Based Edupreneurship in 21st-Century Higher Education - Rifaatussalwa Hayati; Diding Nurdin; Eka Prihatin; Cepi Triatna (AL-ISHLAH: Jurnal Pendidikan, 2024)
The objective of this qualitative descriptive study is to evaluate the effectiveness of the PDCA (Plan, Do, Check, Act) cycle in enhancing the quality of entrepreneurship education, or "edupreneurship," within universities, with a focus on Tangerang Raya University. This research engaged key stakeholders from the university, including the Vice-Rector for Academic and Student Affairs, deans and vice deans of the Faculty of Economics, Business and Humanities, the Faculty of Teacher Training and Education, and the Faculty of Engineering, as well as coordinators of study programs and students participating in edupreneurship initiatives. The findings indicate that the PDCA cycle significantly contributes to the improvement of edupreneurship quality and achievements at Tangerang Raya University. By facilitating the identification of weaknesses, the PDCA cycle enables continuous enhancements in the entrepreneurial education process. Despite its effectiveness, the implementation of the PDCA cycle in edupreneur programs encounters several challenges. These include constraints such as limited resources (budgets, teaching staff, and facilities), implementation hurdles, varying levels of engagement among members, shifting priorities, challenges in identifying opportunities, time limitations, difficulties in impact assessment, collaboration challenges, member turnover, and environmental uncertainties.This study underscores the PDCA cycle's potential in fostering edupreneurship within universities. However, it also highlights the necessity for addressing the aforementioned obstacles to fully leverage the PDCA cycle's capabilities in enhancing the quality of edupreneurship education. Addressing these challenges is essential for the sustained success and effectiveness of edupreneur programs driven by the PDCA quality management cycle.